2010
DOI: 10.1091/mbc.e10-02-0123
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty Proteins Inhibit Receptor-mediated Activation of Phosphatidylinositol-specific Phospholipase C

Abstract: PLCγ03B3 binds Spry1 and Spry2. Overexpression of Spry decreased PLCγ03B3 activity and IP3 and DAG production, whereas Spry-deficient cells yielded more IP3. Spry overexpression inhibited T-cell receptor signaling and Spry1 null T-cells hyperproliferated with TCR ligation. Through action of PLCγ03B3, Spry may influence signaling through multiple receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 70 publications
3
44
1
Order By: Relevance
“…This suggests that Spry4 most likely acts via the PLC-Ca ++ and not the Ras pathway, leading to both inhibition of Ca 2+ mobilisation and inhibition of Erk activation via PKC. It has also recently been shown that murine Spry1 and Spry2 can bind PLC thereby inhibiting the production of IP3 and calcium release in NIH3T3 cells, and that they regulate PLC activity in T cells (Akbulut et al, 2010). Together with our data, these studies suggest that regulation of the PLC-Ca 2+ pathway by Spry proteins plays important roles in various biological contexts.…”
Section: Regulation Of Branching Morphogenesis By Spry Proteinssupporting
confidence: 84%
“…This suggests that Spry4 most likely acts via the PLC-Ca ++ and not the Ras pathway, leading to both inhibition of Ca 2+ mobilisation and inhibition of Erk activation via PKC. It has also recently been shown that murine Spry1 and Spry2 can bind PLC thereby inhibiting the production of IP3 and calcium release in NIH3T3 cells, and that they regulate PLC activity in T cells (Akbulut et al, 2010). Together with our data, these studies suggest that regulation of the PLC-Ca 2+ pathway by Spry proteins plays important roles in various biological contexts.…”
Section: Regulation Of Branching Morphogenesis By Spry Proteinssupporting
confidence: 84%
“…All sprouty proteins were found to be negative regulators of growth factor signaling, especially the MAPK/ERK pathway (32,33). A potential role of sprouty proteins has been seen in T cell activation where both SPRY1 and SPRY2 inhibit T cell activation and IL-2 production (34,38). SPRY1-deficient mice have been shown to have enhanced antitumor T cell responses (39).…”
Section: Discussionmentioning
confidence: 99%
“…Sprouty proteins are a well-conserved family known to mediate the negative feedback regulation of the MAPK pathway (31,32). Sprouty proteins bind to Grb2 and other components of the MAPK pathway, preventing the upregulation of pERK (33,34).…”
Section: Figurementioning
confidence: 99%
“…An antibody against human Spry4 was purchased from Santa Cruz Biotechnology, Inc. (Santa Cruz, CA). Antibodies against mouse Spry1 and Spry2 have been previously described (23). Antibodies against the phosphorylated forms of STAT1, STAT3, ERK1/2 (Thr-202/Tyr-204), and p38 MAPK (Thr-180/Tyr-182), as well as antibodies against ERK1/2 and p38 MAPK, were obtained from Cell Signaling Technology (Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%